2015
DOI: 10.1002/jms.3593
|View full text |Cite
|
Sign up to set email alerts
|

Application of gas chromatography–tandem mass spectrometry (GC/MS/MS) for the analysis of deuterium enrichment of water

Abstract: Incorporation of deuterium from deuterium oxide (2H2O) into biological components is a commonly used approach in metabolic studies. Determining the dilution of deuterium in the body water pool (BW) can be used to estimate body composition. We describe three sensitive GC-MS/MS methods to measure water enrichment in BW . Samples were reacted with NaOH and U-13C3-acetone in an autosampler vial to promote deuterium exchange with U-13C3-acetone hydrogens. Headspace injections were made of U-13C3-acetone-saturated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…And, conversely, in deuterated water, all processes are slowed down not only from the biological point of view within the cell, but also from the point of view of increasing the nonuniformity of water density, which slows down metabolic processes in the environment outside the cell [ 33 ]. Our data correlate with the data of other authors, where similar effects of water of different D/H isotope composition are observed in different systems in vitro and in vivo [ 34 36 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…And, conversely, in deuterated water, all processes are slowed down not only from the biological point of view within the cell, but also from the point of view of increasing the nonuniformity of water density, which slows down metabolic processes in the environment outside the cell [ 33 ]. Our data correlate with the data of other authors, where similar effects of water of different D/H isotope composition are observed in different systems in vitro and in vivo [ 34 36 ].…”
Section: Discussionsupporting
confidence: 92%
“…First of all, that concerns the medicine. It is well known that one of the pharmaceutical trends is the development of deuterium-containing drugs, which are deuterated analogues of already known proton-containing biologically active compounds [ 10 , 11 , 29 , 34 , 42 ]. The second direction refers to the role of deuterium-depleted water as an adjuvant in the treatment of cancer [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…in vitro cell media, mouse drinking water, mouse, and human total body water (urine)), as it can affect isotopic enrichments into DNA as well as potentially alter cellular metabolism 29 . Other investigators using stable heavy water for their research have determined the level in total body water (TBW) 27 , 28 , 30 39 using infrared absorption or by utilizing test methods for plasma and urine, which involve using a metal catalyst (e.g. uranium), high temperatures (e.g.…”
Section: Introductionmentioning
confidence: 99%